Mental Health Crisis Location and Police Transportation Decisions: the Impact of Crisis Intervention Team Training on Crisis Center Utilization - Comartin, Erin B. (Journal of contemporary criminal justice, 2019)
Crisis Intervention Team (CIT) research has shown increases in officer transports of individuals with serious mental illness to emergency departments (ED) which, while more appropriate than incarceration, can be expensive and lack linkage to long-term mental health services. Mental health crisis centers offer a promising alternative, but impact may be limited by proximal distance and lack of officer awareness. To address this concern, this study asked, “Does CIT training affect officer transport decisions to a crisis center over a nearby ED?” Researchers analyzed crisis call reports in a Midwestern county and found increased use of the crisis center and decreased use of EDs by officers after CIT was implemented. The crisis location affected officer transport decisions, yet CIT officers were more likely than non-CIT officers to travel farther for appropriate linkage. Findings suggest CIT changes officer behavior, which could potentially lead to long-term, low-cost treatment for individuals with serious mental illnesses when there is a mental health crisis center.